Exploring the Set-up Process and Structure of Farmer Producer Organisations in Punjab and Haryana (International Journal of Food and Nutritional Sciences, 2023)
Farmer Producer Organisations (FPOs) have been established as an institutional mechanism to overcome challenges related to structural and market constraints faced by small and marginal farmers in India. The present research examines the set-up process, organisational structure, and institutional support mechanisms of FPOs in the states of Punjab and Haryana, with a comparative perspective. The study derives data from a primary survey of 100 representatives of 20 FPOs of Punjab and Haryana. The findings highlight that the FPOs of Haryana enjoy robust institutional assistance, due to the existence of a dedicated promoting agency (SFACH) and financial support through programmes such as the Crop Cluster Development Programme; however, Punjab lags both in institutional support and capital mobilisation. Also, despite the dominance of small and marginal farmers in membership of the FPOs, the shareholding and decision making is highly skewed in favour of medium and large farmers. Effective policy support, hiring professional managers, and strong promoting agencies can be instrumental in enhancing the effectiveness of FPOs.